Services in a development round : three goals and three proposals - Mattoo, Aaditya, 1961- 1961- (Policy research working paper, 2005)
"The benefits of services trade reform are huge but services negotiations in the World Trade Organization (WTO) are making little progress. A proximate cause is the current negotiating process, based on an inertial request-and-offer approach rather than a set of goals that would give direction and momentum to the negotiations. The paper suggests that WTO members should consider: (1) locking in the current openness of cross-border trade for a wide range of services; (2) eliminating barriers to foreign investment either immediately or in a phased manner where regulatory inadequacies need to be remedied; and (3) allowing greater freedom of international movement at least for intra-corporate transferees and for service providers to fulfill specific services contracts. A deeper problem is that WTO members have sought to negotiate market access in services without adequately addressing concerns that the General Agreement on Trade in Services (GATS) commitments limit regulatory freedom unduly and unpredictably, that regulatory institutions in many countries are too weak to cope with liberalized markets, and that there is no provision for the regulatory cooperation that is necessary for successful liberalization, particularly of temporary labor mobility.